Anterior cruciate ligament rupture is associated with abnormal and asymmetrical lower limb loading during walking. Issue 5 (May 2017) - Huang, Hongshi; Keijsers, Noël; Horemans, Herwin; Guo, Qinwei; Yu, Yuanyuan; Stam, Henk; Praet, Stephan; Ao, Yingfang
Abstract: Objectives: Anterior Cruciate Ligament (ACL) deficiency may result in abnormal lower limb loading with increased foot pronation. This study evaluated spatiotemporal parameters and plantar pressure distribution during walking in participants with and without an ACL rupture. Design: Cross-sectional. Methods: Plantar pressure was measured in 42 unilateral ACL deficient (ACLD) participants and 32 healthy controls while walking barefoot. Spatiotemporal parameters, pressure distribution and center of pressure (CoP) during foot roll off were determined. Differences in spatiotemporal parameters and pressure distribution were analyzed using a Linear Mixed Model. CoP position was analyzed with one-way ANOVA. Results: ACLD participants had a longer contact time and earlier forefoot contact compared to controls. The ACLD side showed a shorter contact time and a faster roll off toward the forefoot compared to the ACL intact side. Compared to controls, ACLD participants had increased pressure under the medioproximal side of the midfoot. Within ACLD participants, the ACLD side had decreased pressure under the heel and increased pressure under the forefoot. Foot pronation was not different between groups or within ACLD participants. CoP of the ACLD participants was significantly more toward the toes during initial contact and toward the heel during foot flat. Conclusions: Changes in lower limb loading during barefoot walking in ACLD participants are due to changes in roll off pattern, most likely in order to reduce anterior shear forces on the knee. Dynamic plantar pressure measurements may assist in evaluating and guiding interventions aimed at normalizing lower limb and knee biomechanics in ACL deficiency.